KAJIAN ESTETIS KANTONG PLASTIK BEKAS SEBAGAI PRODUK FASHION (DOMPET) (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
Plastic bags are disposable items with irresponsible post-consumption activities. Arde Wiyasa's concern is that because there is more and more plastic waste in the world, finally there is a desire to reduce plastic waste by making used plastic bags a product with high selling value and can be used in everyday life without polluting the environment. Because of this problem, Arde Wiyasa began to look at plastic bag waste as a material for making fashion products, namely wallets. Because Arde Wiyasa's wallet, which is made from used plastic bags, is an art product, discussing a work of art is about the beauty contained within. The knowledge used to examine and discuss art and beauty is aesthetics. The aesthetic values ​​of wallets made from used plastic bags can be seen from two sides, namely the form and the meaning. In terms of shape, Arde Wiyasa's plastic wallet is a harmonious arrangement of visual elements (lines, colors, textures) in a beautiful unity. Meanwhile, the values ​​of meaning radiate from the pictures and writings added by Arde Wiyasa which convey meaning, namely an invitation or appeal to reduce the use of plastic bags Keywords: Used Plastic Bags, Wallets, Aesthetics